Lactic acid production from glucose and xylose using the lactogenic Escherichia coli strain JU15: Experiments and techno-economic results. (February 2019) - Parra-Ramírez, Daniela; Martinez, Alfredo; Cardona, Carlos Ariel
Highlights: Lactic acid is produced from xylose and glucose using a genetically modified strain. The modified strain presents yields very close to the theoretical. The process was simulated to develop a technical and economic analysis. The scale of production has great influence on the distribution of costs. The industrial implementation of the strain is possible due to its versatility. Abstract: In this work, d -lactic acid production was evaluated from a simulated hydrolysate of corn stover (32 g/L xylose, 42 g/L glucose) with the metabolically engineered Escherichia coli strain JU15. Based on the experimental results, a technical and economic analysis of the entire process was performed using the Aspen Plus software. As a result, it was possible to show that the strain can efficiently produce lactic acid from both sugars, reaching a final concentration of 40 g/L and a yield of 0.6 g lactic acid/g sugars. The process is economically viable at higher scales of 1000 tons/day. The cost distribution is influenced by the scale of the process; on a larger scale, the cost of raw materials represents a higher percentage of total cost than it does on smaller scales. The use of a metabolically engineered strain allows a better use of the sugars obtained from agroindustrial residues.